Judging uncertainty: the case of the court of justice of the European Union (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The contribution aims to analyze the jurisprudence of the CJUE in the scientific-technical field. The thesis put forward is that the CJEU usually does not seek elements or data on its own to assess the merits of the scientific opinion challenged, preferring to operate an external review of the legitimacy of the contested act that is based on that opinion, aimed at excluding that there has been excess of power on the part of those who adopted it. And yet, it is also shown how in the jurisprudence of Luxembourg there is nevertheless a “scientific” protagonism when it is necessary to offer interpretation to dubious concepts.
Keywords: Courts and science; CJEU; judicial review; experts; scientific advisory